INTEGRATING CHARACTER BUILDING INTO TEACHING TO ENHANCE THE STUDENTS ENVIRONMENTAL AWARENESS - Setyowati, Lestari (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2013)
Due to the growing environmental destruction, it is becoming necessary for people to start to care about the place they live. One way of doing this is through education by making the students aware of their environmental problems. However, the character education in IndonesiaÂ Â focuses more on improving the quality within and between individuals, and seems to neglect the characters, which shows relationship with environment. Creating students who are environmentally aware and able to take participation to protect their environment basically helps them to posses good moral values. In short, possessing characters which signifies awareness to environmental problems and ability to protect the environment is as important as possessing desirable characters that can help students to succeed in live. This paper discusses about the characters building within Indonesian context, environmental education, language learning and environmental education, and some proposed models to integrate environmental education into teaching.Keywords: character building, environmental education, models